Keterpenuhan Penggunaan Kriteria Dan Indikator Global Sustainable Tourism Council (Gstc) Dalam Peningkatan Ekonomi Masyarakat Lokal - Hatibie, Irma Kharisma; Dai, Srilian Laxmiwaty (JURNAL DESTINASI PARIWISATA, 2021)
The emergence of the concept of tourist villages in various regions in Indonesia has become a stimulus for other villages to compete to make their villages into tourist villages that are competitive and prosper rural communities through tourism activities. This has an impact and is also used in the development of the Kembang Arum tourist village in Sleman Regency, Yogyakarta. Therefore, in order to improve the quality of tourist villages, the use of the GSTC indicator can be a reference for improving the quality of a tourist destination. The purpose of this study was to measure the quality of the Kembang Arum tourist village in Sleman Regency whether it was in accordance with the GSTC indicators as criteria and measurements of a standardized tourist destination. The research method used is descriptive qualitative with content analysis techniques and makes interpretations of the results of interviews and observations. The results of this study are that the Kembang Arum tourist village has fill the requirements as a tourist destination, according to GSTC criteria and indicators. This research proving that criteria and indicators of GSTC already being a reference and continue to be used to measure the quality of the destination gradually. Keywords: Desa wisata, GSTC, Ekonomi Masyarakat Lokal, Kembang Arum.